1999
DOI: 10.1073/pnas.96.23.13247
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the mammalian postcranium: A developmental perspective

Abstract: The past two decades have greatly improved our knowledge of vertebrate skeletal morphogenesis. It is now clear that bony morphology lacks individual descriptive specification and instead results from an interplay between positional information assigned during early limb bud deployment and its ''execution'' by highly conserved cellular response programs of derived connective tissue cells (e.g., chondroblasts and osteoblasts). Selection must therefore act on positional information and its apportionment, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 61 publications
(33 reference statements)
0
129
0
Order By: Relevance
“…This study also supports theoretical proposals based on recent advances in evolutionary developmental biology that anatomical regions can be understood functionally only when they are considered as units that are integrated by developmental and mechanical constraints (31). Whenever possible, hypotheses of integration should be established empirically, and, as illustrated here, geometric morphometric techniques adapted to deal with articulated structures can aid these investigations.…”
Section: Discussionmentioning
confidence: 62%
“…This study also supports theoretical proposals based on recent advances in evolutionary developmental biology that anatomical regions can be understood functionally only when they are considered as units that are integrated by developmental and mechanical constraints (31). Whenever possible, hypotheses of integration should be established empirically, and, as illustrated here, geometric morphometric techniques adapted to deal with articulated structures can aid these investigations.…”
Section: Discussionmentioning
confidence: 62%
“…These two approaches are proving productively complementary to each other (128,129) and can be integrated with the expanding fossil record. Fossils provide the necessary temporal dimension to the study of evolutionary developmental biology (4,8,48,97). The integration of fossils and genetics has already successfully yielded broad insights at higher taxonomic levels.…”
Section: The Futurementioning
confidence: 99%
“…Many developmental processes of bone and enamel development are highly conserved (48,(125)(126)(127). It has also been shown that genes underlying intraspecific variation can determine interspecific variation (68).…”
Section: An Integrative Approachmentioning
confidence: 99%
“…A now classic example of the use of a developmental perspective in systematics is that of Davis (40), who was able to show based on a developmental approach to morphology that giant pandas were related to bears rather than to lesser pandas, a result amply confirmed subsequently with genetic data (41). The rapidly expanding understanding of developmental processes can reduce subjectivity in describing complex morphologies and help us describe better characters (39,42 Another recent approach to the problem involves so-called total evidence (43). This approach proposes to use all available characters, morphological and genetic.…”
mentioning
confidence: 78%